O cruzeiro: acontecimento e rotina como forma de vida da mulher nos anos 1950 - Nascimento, Edna Maria Fernandes dos Santos [UNESP] (My University, 2012)
Magazines such as O Cruzeiro are part of the Brazilian collection. In its pages, the female presence is constant. From the concepts of Greimas’ way of life and happening and routine from Zilberberg, we analyse a photoreport which highlights the actress Ilka Soares, comparing her to texts of the session “To the woman”. The analysis of such texts lets us verify the behaviour of a distinguished professional which is different from the traditional model of the housewife of the fifties. Reconstitute the ways of life of these women is to make up for the memory of the country

Revistas como O Cruzeiro fazem parte do acervo da história do Brasil. Nas páginas do periódico, a presença feminina é uma constante. A partir dos conceitos de forma de vida, de Greimas, e de acontecimento e rotina, de Zilberberg, analisamos uma fotorreportagem que destaca a atriz Ilka Soares, comparando-a com textos da coluna “Para a mulher”. A análise desses textos nos permite verificar o comportamento de uma profissional de destaque que se diferencia do modelo de uma forma de vida tradicional da dona de casa da dé- cada de 50 do século XX. Reconstituir as formas de vida dessas mulheres é recuperar a memória do país.
O Cruzeiro: happening and routine as a way of life of the woman at the fifties
Keywords: Woman; Way of life; Happening; Routine; O Cruzeiro; Mulher; Forma de vida; Acontecimento; Rotina; O Cruzeiro